PENGARUH MEDIA VIDEO ANIMASI TERHADAP HASIL BELAJAR IPAS MATERI SIKLUS AIR PADA SISWA KELAS V SD GMIT KUANINO 3 KOTA KUPANG - Hali, Antonius Suban; Andriyani A. Dua Lehan; Nofrianti Y. Liunokas (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to find out whether animated video media has a significant influence on science learning outcomes regarding the water cycle in class V students at SD GMIT Kuanino 3, Kupang City. The type of research used is Quasi Experimental Design. The sampling technique used was purposive sampling technique with a sample size of 11 people. The research results prove that there is a significant influence between animated video media on student learning outcomes. This is proven by the difference in students' completeness scores before being given treatment (pretest) and after being given treatment (posttest). There were 2 students who completed the pretest, while 11 students completed the posttest, so it can be said that the use of animated video media regarding the water cycle can improve student learning outcomes. The normality test of learning outcomes from the pretest-posttest obtained a significant value of 0.200 for the pretest and 0.127 for the posttest > 0.05 so that the data was normally distributed, the homogeneity test results showed (sig) Levene's of 0.438 > 0.05 so the data obtained was homogeneous. Apart from that, testing the hypothesis with the t test using SPSS version 25 obtained a significance value (2-tailed) 0.000 < 0.05. Thus, animated video media has a significant influence on student learning outcomes.